2007
DOI: 10.1021/jp073980j
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Coupled with UV Spectral Evidence for Near-Irreversible Nonionic Micellar Binding of N-Benzylphthalimide under the Typical Reaction Conditions:  An Observation Against a Major Assumption of the Pseudophase Micellar Model

Abstract: Pseudo-first-order rate constants (k(obs)) for alkaline hydrolysis of N-benzylphthalimide (1) show a nonlinear decrease with the increase in [C(m)E(n)]T (total concentration of Brij 58, m = 16, n = 20 and Brij 56, m = 16, n = 10) at constant [CH(3)CN] and [NaOH]. These nonionic micellar effects, within the certain typical reaction conditions, have been explained in terms of the pseudophase micellar (PM) model. The values of micellar binding constants (KS) of 1 are 1.04 x 10(3) M(-1) (at 1.0 x 10(-3) M NaOH) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 31 publications
(43 reference statements)
1
28
1
Order By: Relevance
“…Recently, similar near irreversible micellar trapping of N-benzylphthalimide (5) was obtained in the alkaline hydrolysis of 5 in the presence of C 16 E 10 and C 16 E 20 micelles [12]. But the values of R t were 88 and $5 at respective 1.0 and 0.76 mM NaOH for C 16 E 10 as well as 140 at 1.0 mM NaOH for C 16 E 20 [12]. In all these studies [9][10][11][12], the observed data, obtained at R < R t , have been explained in terms of PM model.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…Recently, similar near irreversible micellar trapping of N-benzylphthalimide (5) was obtained in the alkaline hydrolysis of 5 in the presence of C 16 E 10 and C 16 E 20 micelles [12]. But the values of R t were 88 and $5 at respective 1.0 and 0.76 mM NaOH for C 16 E 10 as well as 140 at 1.0 mM NaOH for C 16 E 20 [12]. In all these studies [9][10][11][12], the observed data, obtained at R < R t , have been explained in terms of PM model.…”
Section: Introductionmentioning
confidence: 66%
“…But the values of R t were 88 and $5 at respective 1.0 and 0.76 mM NaOH for C 16 E 10 as well as 140 at 1.0 mM NaOH for C 16 E 20 [12]. In all these studies [9][10][11][12], the observed data, obtained at R < R t , have been explained in terms of PM model. The unusual near irreversible trapping of moderately hydrophobic reactants by C m E n micelles at R P R t cannot be attributed to the usual shielding effect of micelles [12].…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations